Sur les points singuliers des fonctions, représentables par les séries de Dirichlet - Oskolkov, L. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. А. Осколков. Об особых точках функций, представимых рядами ДирихлеL. Oskolkovas. Funkcijų, išreiškiamų Dirichle eilutėmis, pavieniai taškai